Disk precession of V603 Aql in 2001-2002 - Suleimanov, V. F.; Bikrnaev, I. F.; Belyakov, C. V.; Sakhibullin, N. A.; Zhukov, G. V.; Aslan, Z.; Kizilogly, U.; Kharnitov, I. (Одеські астрономічні публікації, 2017)
The rezults of the novalike variable V603 Aql photometric observations performed by Russian-Turkish telescope RTT150 during 11 nights of 2001 - 2002 are presented. It is shown the star was in the state with ”positive” superhumps and photometric period 0.d144 - 0.d145 was longer than orbital one. The conclusion that disc precession period depends on the accretion rate has been made. It is found that V603 Aql in the state with ”negative” superhumps is brighter by 0.m2 - 0.m3 than in the state with ”positive” superhumps. It is suggested that transition between these states is also caused by accretion rate changing. Quasiperiodic oscillations (QPO) of the brightness with typical periods 9 - 70 min are found for the each night.